Folktales and Short Stories to Blend Culture and Language Competence - Olivares, Cinthya (2020)
The aim of this research is to study the use of literature-based cultural material to reinforce speaking and writing skills by using folktales (general culture) and short stories (home culture) in oral and written expression in the English Teaching major. The analysis of a questionnaire for teachers and students indicates that those texts are rarely used to strengthen the productive skills. Based on this, a proposal has been devised to blend world and home culture with language competence to develop written and oral activities in the classroom.